2023
DOI: 10.1108/ijppm-06-2022-0305
|View full text |Cite
|
Sign up to set email alerts
|

Examining high-performance work practices in academia: role of administrative workload and support staff

Abstract: PurposeThe study aims to explore the effectiveness of performance-oriented practices like high-performance work practices (HPWPs) in higher education (HE), given its explicit focus on performance these days.Design/methodology/approachThe study uses hierarchical linear modeling using statistical package for social sciences (SPSS 22.0) to test the hypotheses. An intertwined framework of the ability–motivation–opportunity (AMO) model and the job demand-resources (JD-R) model was proposed. The study considered str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 101 publications
0
1
0
Order By: Relevance
“…Based on findings, it showed that there is a significant and weak relationship between workload and employee performance. This finding supported by Aparna & Sahney (2023) stated that heavy workload may become the prime source of anxiety and stress in an organization, negatively affecting the quality of their work and morale. Organizations with moderate workloads are more likely to work effectively than faculties with higher workloads (Ayeni & Amanekwe, 2018).…”
Section: Discussionmentioning
confidence: 57%
“…Based on findings, it showed that there is a significant and weak relationship between workload and employee performance. This finding supported by Aparna & Sahney (2023) stated that heavy workload may become the prime source of anxiety and stress in an organization, negatively affecting the quality of their work and morale. Organizations with moderate workloads are more likely to work effectively than faculties with higher workloads (Ayeni & Amanekwe, 2018).…”
Section: Discussionmentioning
confidence: 57%